2006
DOI: 10.1093/jxb/erl242
|View full text |Cite
|
Sign up to set email alerts
|

Members of the ethylene signalling pathway are regulated in sugarcane during the association with nitrogen-fixing endophytic bacteria

Abstract: Nitrogen-fixing bacteria have been isolated from sugarcane in an endophytic and beneficial interaction that promotes plant growth. In this work, for the first time, the involvement of ethylene signalling in this interaction was investigated by molecular characterizing members of this pathway in sugarcane. The expression pattern of a putative ethylene receptor (SCER1) and two putative ERF transcription factors (SCERF1 and SCERF2) show exclusive modulation in plants inoculated with the diazotrophic endophytes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 50 publications
4
43
0
2
Order By: Relevance
“…The ethylene receptor SCER1 and the transcription factor SCERF2 are induced after inoculation, while SCERF1 is repressed in inoculated plants. These genes showed an opposite expression profile in response to pathogens, and are differentially regulated in sugarcane contrasting BNF genotypes (Cavalcante et al 2007). The data suggest that specific components of ethylene signaling pathways may identify a beneficial endophytic association, modulating plant response to diazotrophic endophytes.…”
Section: Sugarcane Defense Responsesmentioning
confidence: 87%
See 1 more Smart Citation
“…The ethylene receptor SCER1 and the transcription factor SCERF2 are induced after inoculation, while SCERF1 is repressed in inoculated plants. These genes showed an opposite expression profile in response to pathogens, and are differentially regulated in sugarcane contrasting BNF genotypes (Cavalcante et al 2007). The data suggest that specific components of ethylene signaling pathways may identify a beneficial endophytic association, modulating plant response to diazotrophic endophytes.…”
Section: Sugarcane Defense Responsesmentioning
confidence: 87%
“…It comprises five distinct classes that share common structural features such as a leucine-rich repeat (LRR) motif or a serine-threonine kinase domain. 280 putative R-genes were identified in the sugarcane EST collection, including in the libraries of plants inoculated with G. diazotrophicus and H. rubrisibalbicans, with the highest percentage of ESTs belonging to Class I (Pto-like) followed by Class II (NBS-LRR) and Class V (LRR-RLK) R-genes (Wanderley- Nogueira et al 2007). Microarray analysis also identified four R-genes responsive to sugarcane association with Herbaspirillum spp.…”
Section: Sugarcane-endophytic Recognitionmentioning
confidence: 99%
“…The endophytic G.d is being used for biopriming of sugarcane plants because its role as promoting plant growth and as resistance-inducer to the systemic pathogenic bacteria Xanthomonas albilineans (Arencibia et al, 2006). For sugarcane, the expression pattern of a putative ethylene receptor (SCER1) and two putative ERF transcription factors (SCERF1 and SCERF2) show differential response to interactions with pathogenic and beneficial microorganisms, suggesting that it might participate in specific ethylene signaling cascade(s) that can identify a beneficial or pathogenic interaction (Cavalcante et al, 2007). The differential expression of TDFs corresponding to the ethylene-signaling pathway could be also related with improved ability of the G.d infection and support the finding that phenolic metabolites prime sugarcane plants during micropropagation in TIBs .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that endophytic diazotrophic bacteria colonize the intercellular spaces and vascular tissues of sugarcane organs, without triggering any symptoms in the plant. The signaling mechanisms are as yet poorly understood but Cavalcante et al (6) suggested that the ethylene signaling pathway may play a role in the establishment of the association between sugarcane and endendophytic diazotrophic bacteria. However, there is little evidence so far that G. diazotrophicus is actually a N2-fixing symbiont of sugarcane or that it even expresses active nitrogenase in plants (13).…”
mentioning
confidence: 99%